The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2319/061917-406.1
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison of treatment effects of total arch distalization using modified C-palatal plate vs buccal miniscrews

Abstract: Comparing the treatment effects between MCPP appliances and buccal miniscrews, the MCPP appliances showed greater distalization and intrusion with less distal tipping of the first molar and less extrusion of the incisor compared to the buccal miniscrews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 26 publications
7
33
0
Order By: Relevance
“…The mini-implant thus placed on the palatal aspect was stable at the end of treatment and did not show any signs of failure. The treatment outcome was similar to the other existing studies [4,5] using palatal mini-implant which showed distalization and intrusion of the maxillary first molar, improvement in nasolabial angle and upper lip retraction. Although the overbite in the present case was only 1mm at the start of treatment, intrusion of the maxillary dentition did not result in an open bite probably because of the counter-clockwise rotation of the mandible.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The mini-implant thus placed on the palatal aspect was stable at the end of treatment and did not show any signs of failure. The treatment outcome was similar to the other existing studies [4,5] using palatal mini-implant which showed distalization and intrusion of the maxillary first molar, improvement in nasolabial angle and upper lip retraction. Although the overbite in the present case was only 1mm at the start of treatment, intrusion of the maxillary dentition did not result in an open bite probably because of the counter-clockwise rotation of the mandible.…”
Section: Discussionsupporting
confidence: 86%
“…To overcome this problem mini-implant may be placed on the palatal aspect where there was thick keratinized mucosa, sufficient cortical bone thickness, interradicular bone width and thickness. Existing literature shows that the modified 'C' palatal plate and modified palatal anchorage plate was the only appliance that brought about group distalization [5,6]. However, these appliances are bulky requires elaborate lab work and increased patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 The introduction of miniscrew implants made skeletal anchorage more easily accessible for the orthodontist. 16 Miniscrew implants can be loaded directly 15,17 or through scaffolding 18,19 and have been shown to enable distal movement of the molars and premolars at the same time, 20,21 causing minimal distal tipping of the molars 21,22 which suggests high stability. However, throughout a lifetime, permanent molars exhibit mesial migration, 23 attributed to the anterior component of force, which is explained to result from mesial inclination of teeth.…”
Section: Introductionmentioning
confidence: 99%